2004
DOI: 10.1097/00008571-200402000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The human 8-oxoguanine DNA N-glycosylase 1 (hOGG1) DNA repair enzyme and its association with lung cancer risk

Abstract: These results suggest that the hOGG1 Ser326Cys polymorphism plays an important role in the risk for lung cancer and is linked to exposure to tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 31 publications
2
74
0
Order By: Relevance
“…Results of a number of studies examining the role of the hOGG1 Ser326Cys polymorphism in lung cancer susceptibility conducted to date have been inconsistent. [7][8][9][10][11][12]17 Our case-control study showed a significant association between hOGG1 Ser326Cys polymorphism and lung cancer overall, supporting the potential effect of this polymorphism on lung cancer susceptibility. Because the question of whether the effect of this polymorphism differed by histology remained unanswered, we also conducted a meta-analysis with consideration to histology.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Results of a number of studies examining the role of the hOGG1 Ser326Cys polymorphism in lung cancer susceptibility conducted to date have been inconsistent. [7][8][9][10][11][12]17 Our case-control study showed a significant association between hOGG1 Ser326Cys polymorphism and lung cancer overall, supporting the potential effect of this polymorphism on lung cancer susceptibility. Because the question of whether the effect of this polymorphism differed by histology remained unanswered, we also conducted a meta-analysis with consideration to histology.…”
Section: Discussionsupporting
confidence: 56%
“…Among the 65 papers identified through this process, 7 were considered eligible. 5,[7][8][9][10][11]17 Two investigators (TO and KM) abstracted the data independently. We used OR from a random-effect model as a summary statistic for association.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mechanism of carcinogenesis in the lung tissue may involve tissue damage and regeneration in the presence of a high ROS release from inflammatory cells that can interact with DNA in epithelial cells to produce permanent genomic mutations (27). One of them, 8-OHG is a mutagenic and most common oxidative modification of guanine, and has a pivotal role in the development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8-OxoG itself is mildly mutagenic and forms G:C → T:A transversion mutations approximately half the time during DNA replication in vitro (22,(30)(31)(32)(33) but only about 5% of the time in vivo (31). The hOGG1 base excision repair pathway is the primary route for the excision and repair of 8-oxoG in human DNA, and genetic polymorphisms of this repair enzyme have been associated with increased risk of lung cancer (50). However, Ogg1 knockout mice have shown no change in the observable phenotype relative to wild-type mice, although a slight increase in mutation rate was observed in some tissues (51,52).…”
Section: Formation Of 8-oxog In the Cr(vi)/asc Oxidation Reactionmentioning
confidence: 99%